The Comparison Of Chicken Farming Business On Various Patterns In North Bengkulu Regency - Harianto Harianto; Nyayu Neti Arianti; Putri Suci Asriani (Agric, 2019)
This study aims to calculate and compare the income and the level of efficiency of poultry farming with various business patterns, namely "Mandiri" or independent, partnering with national company and partnering with foreign company. Respondents were taken in a census method, consist of 11 independent farmers, 21 farmers who partnered with national company and 10 farmers who partnered with foreign company. Income is calculated by subtracting revenue and costs. Business efficiency is determined by the R/C Ratio. Meanwhile, the comparison of incomes were analyzed by the t-test. The results showed that the average income of independent livestock business is IDR 5.536,95/head, the national partnership is IDR 2.523,20/head, and those with foreign partner is IDR 3.162,74/head. While The efficiency level of independent pattern is 1,15, 1,09 for national partnership pattern and 1,10 for foreign partnership. The results of the t-test at the 95% confidence level indicate that the income of independent livestock is higher than those in nationally and foreign-partnered farms. While the nationally-partnered business is not higher than the foreign-partnered.